2010
DOI: 10.1073/pnas.0907922106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast photochemistry of methyl hydroperoxide on ice particles

Abstract: Simulations show that photodissociation of methyl hydroperoxide, CH 3 OOH, on water clusters produces a surprisingly wide range of products on a subpicosecond time scale, pointing to the possibility of complex photodegradation pathways for organic peroxides on aerosols and water droplets. Dynamics are computed at several excitation energies at 50 K using a semiempirical PM3 potential surface. CH 3 OOH is found to prefer the exterior of the cluster, with the CH 3 O group sticking out and the OH group immersed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…78 Even if these free radicals manage to escape from the solvent cage, secondary reactions would generally result in smaller products relative to the size of the precursor peroxide compound, which would consequentially also reduce the average C value.…”
Section: Resultsmentioning
confidence: 99%
“…78 Even if these free radicals manage to escape from the solvent cage, secondary reactions would generally result in smaller products relative to the size of the precursor peroxide compound, which would consequentially also reduce the average C value.…”
Section: Resultsmentioning
confidence: 99%
“…90,[186][187][188] Radical recombination reactions are strongly affected by surface water and ice where reactions are enhanced. 189 The mechanism and role of water in some of these instances remains uncertain as pointed out for photochemical reactions of aromatic molecules on ice which however do not occur on liquid water. 190 Adsorbed water on surfaces of oxide and mineral dust aerosols were characterized in insightful experiments by Grassian et al and shown to alter and enhance reactivity of O 3 , H 2 CO 3 and HNO 3 .…”
Section: Cluster Models For Condensed Phases Aerosols and Interfacesmentioning
confidence: 99%
“…7 Moreover, among the complexes formed by MHP, only several representatives are considered. From experimental study, 8 it follows that the water solubility of MHP is not high in comparison with H 2 O 2 (the corresponding Henry's constant of MHP is approximately 200 times lower than for H 2 O 2 ).…”
Section: ' Introductionmentioning
confidence: 99%